PENGARUH KUALITAS PELAYANAN PUBLIK DAN DISIPLIN KERJA TERHADAP KEPUASAN MASYARAKAT - Muafatun; Muhammad Syaifulloh; Hendri Sucipto (Lembaga Pengembangan Kinerja Dosen, 2022)
The quality of public services and work discipline are one of the factors that affect people's satisfaction. The purpose of this study is to determine the partial and simultaneous influence of the quality of public services and work discipline on the satisfaction of the people of Cimohong Village. The population in this study is the people of Cimohong Village who have interests in the Cimohong Village Office which amounts to 1464 people. For the sampling of the study, the researchers used the Slovin technique, then the sample used was 95 people. Data collection techniques use questionnaires and documentation. Test the validity of the instrument using Product Moment correlation and reliability test using Cronbach's Alpha. The classical assumption test consists of a normality test, a multicollinearity test and a heteroskedasticity test. The hypothesis test consists of a partial test (t test), a simultaneous test (an F test) and a multiple linear regression test. The results showed that: (1) there was a positive and significant influence on the quality of public services on community satisfaction by calculating 3,208 > 1,661 at a significance level of 5%; (2) there is a positive and significant influence of work discipline on community satisfaction with a calculation of 3,666 > of 1,661 at a significance level of 5%; (3) there is a positive and significant influence on the quality of public services and work discipline simultaneously on community satisfaction with a calculated value of 17,519> an Ftabel value of 3.94 at a significance level of 5%.